2019
DOI: 10.1186/s13071-018-3256-z
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevalence and ecotypes of Anaplasma phagocytophilum in moose Alces alces, red deer Cervus elaphus, roe deer Capreolus capreolus and Ixodes ricinus ticks from Norway

Abstract: BackgroundThe geographical expansion of the tick Ixodes ricinus in northern Europe is a serious concern for animal and human health. The pathogen Anaplasma phagocytophilum is transmitted by ticks and causes emergences of tick-borne fever (anaplasmosis) in livestock. The transmission dynamics of the different ecotypes of A. phagocytophilum in the ecosystems is only partly determined. Red deer and roe deer contribute to circulation of different ecotypes of A. phagocytophilum in continental Europe, while the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
273
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(296 citation statements)
references
References 41 publications
18
273
5
Order By: Relevance
“…Sm16 attenuated the pro-inflammatory responses of LPS-stimulated macrophages compared to LPS controls in a dose-dependent manner. This observation suggested that Sm16 (34-117) exposure arrests macrophage responses to TLR4 activation and is supported by the anti-inflammatory activity of Sm16-derived molecules, and other HDMs, in dampening responses to LPS [13,14,17,19,20,22,24,26,40,[50][51][52]. Our results also confirm that the chemically synthesized Sm16 (34-117) retains the anti-inflammatory properties of Sm16 (and also binds anti-Sm16 antibodies in infected mice blood).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Sm16 attenuated the pro-inflammatory responses of LPS-stimulated macrophages compared to LPS controls in a dose-dependent manner. This observation suggested that Sm16 (34-117) exposure arrests macrophage responses to TLR4 activation and is supported by the anti-inflammatory activity of Sm16-derived molecules, and other HDMs, in dampening responses to LPS [13,14,17,19,20,22,24,26,40,[50][51][52]. Our results also confirm that the chemically synthesized Sm16 (34-117) retains the anti-inflammatory properties of Sm16 (and also binds anti-Sm16 antibodies in infected mice blood).…”
Section: Discussionsupporting
confidence: 79%
“…In the report of the discovery of the Sj16 homolog in S. japonicum, Hu et al [18] states that this molecule 'shares 99% identity with Sm16 in its nucleotide sequence, and 100% identity in its protein sequence'. A recombinant formulation of the molecule was produced, termed rSj16, and has been used in a number of studies [18][19][20][21][22][23][48][49][50][51][52]. We show here with our in-depth analysis of the genomic data currently available that while Sm16 represents a single copy gene in S. mansoni, three Sm16-like molecules exist in the genome of S. japonicum; however, none of the three Sj16s share 100% primary sequence identity with Sm16.…”
Section: Discussionmentioning
confidence: 97%
“…There are very few studies on α2M in tick feeding physiology. Two studies have reported involvement of α2M in immune defense of soft ticks [81] and antimicrobial activity in I. ricinus [82].…”
Section: A) a Americanum Tick Saliva Contains A Large Diversity Of Pmentioning
confidence: 99%
“…Feeding and digestion of large amounts of host blood exposes ticks to hydroxyl radicals and reactive oxygen species (ROS), which if left uncontrolled could damage tick tissue [121,122]. Expression of antioxidant proteins protect the tick during feeding and digestion of the blood meal.…”
Section: E) Ticks Inject Multiple Antioxidant Proteins Into the Feedimentioning
confidence: 99%
“…The main protein component of yolk in P. vannamei zygotes is vitellin, a large multi-subunit lipo-glyco-caroteno-protein; its degraded products are the source of amino acids and other nutrients for development in the non-feeding larvae (see Fig 1) [41], which survival depends on the nutrient reserves of the yolk [42]. P. vannamei cysteine peptidase activity is high at the naupliar stages (Fig 3A), we presume this activity is responsible for hydrolysis of yolk proteins, as described in other arthropods [43][44][45]. Cathepsin L, cathepsin C and calpain are assumed to be the main enzymes responsible of the hydrolysis of vitellin given their significantly higher expression at naupliar stages (clustered in Figs 2 and 3B-3D, respectively).…”
Section: Discussionmentioning
confidence: 62%